Molecular cloning, sequence analysis and expression pattern of hepcidin gene in ayu (Plecoglossus altivelis) - Chen, Mei-Zhen; Jiong, Chen; Lu, Xin-Jiang; Shi, Yu-Hong (Kunming Institute of Zoology, Chinese Academy of Sciences, 2011)
Hepcidin, a member of cysteine-rich antimicrobial peptides, plays an important role in both fish adaptive regulation of iron metabolism. In this paper, the nucleotide sequence of a full-length cDNA clone for ayu (Plecoglossus altivelis) hepcidin gene, 763 nucleotides in length, was determined. Ayu hepcidin gene contained a complete open reading frame (ORF) encoding an 85-amino-acid peptide with a molecular weight of 9.7 k. A signal peptide of 24 residues existed in hepcidin N-terminus. The ayu hepcidin mature peptide sequence contained 25 amino acids with eight cysteines that formed four disulfide bonds. Sequence comparison and phylogenetic analysis showed that ayu hepcidin was most similar to Atlantic salmon (Salmo salar), and the relationships of the different hepcidin coincided well with the evolutionary relationships of their organisms. In healthy ayu, hepcidin mRNA was mainly expressed in the liver, spleen, kidney, heart, and muscle. After Listonella anguillarum infection, liver hepcidin mRNA expression change was determined by quantitative real-time PCR (qRT-PCR) method. Hepcidin transcripts of ayu liver were significantly up-regulated and peaked at 12 h. These results suggest that hepcidin may be involved in the immune response of ayu.